Computational determination of the effects of virulent Escherichia coli and salmonella bacteriophages on human gut. Issue 135 (October 2016) - Mostafa, Marwa Mostafa; Nassef, Mohammad; Badr, Amr
Highlights: This research paper presents a novel system for detecting the effects of bacteriophages on human gut. The system studied the effects of bacteriophages that infect Escherichia coli O157:H7, E. coli O104:H4 and Salmonella typhimurium on human gut. Enterobacteria phage 933W, Enterobacteria phage VT2-Sa and Enterobacteria phage P22 which are bacteriophages that infect E. coli O157:H7, E. coli O104:H4 and S. typhimurium, were chose to study its effect on seven bacterium families exist in human gut. Three interactions, the bacteriophages proteins and the human gut bacterium strains proteins were detected. From the resulted interactions, several effects were detected such as: antibacterial activity against a number of bacterial species in human gut, regulation of cellular differentiation and organogenesis during gut, lung, and heart development, ammonia assimilation in bacteria, yeasts, and plants, energizing defense system and its function in the detoxification of lipopolysaccharide, and in the prevention of bacterial translocation in human gut. Abstract: Background and objective: Salmonella and Escherichia coli are different types of bacteria that cause food poisoning in humans. In the elderly, infants and people with chronic conditions, it is very dangerous if Salmonella or E . coli gets into the bloodstream and then they must be treated by phage therapy. Treating Salmonella and E . coli by phage therapy affects the gut flora. This research paper presents a system for detecting the effects of virulent E . coli and Salmonella bacteriophages on human gut. Methods: A method based on Domain–Domain Interactions (DDIs) model is implemented in the proposed system to determine the interactions between the proteins of human gut bacteria and the proteins of bacteriophages that infect virulent E . coli and Salmonella. The system helps gastroenterologists to realize the effect of injecting bacteriophages that infect virulent E. coli and Salmonella on the human gut. Results: By testing the system over Enterobacteria phage 933W, Enterobacteria phage VT2-Sa and Enterobacteria phage P22, it resulted in four interactions between the proteins of the bacteriophages that infect E. coli O157:H7, E. coli O104:H4 and Salmonella typhimurium and the proteins of human gut bacterium strains. Conclusion: Several effects were detected such as: antibacterial activity against a number of bacterial species in human gut, regulation of cellular differentiation and organogenesis during gut, lung, and heart development, ammonia assimilation in bacteria, yeasts, and plants, energizing defense system and its function in the detoxification of lipopolysaccharide, and in the prevention of bacterial translocation in human gut.